One-member sentences in the novel “Maria” by Ulas Samchuk: typology and functions (Linguostylistic Studies, 2020)
The article elucidates the stylistic features of one-member sentences in the novel Maria by Ulas Samchuk. In modern theoretical studies on syntax, the issue of one-member sentences is still hotly debated and topical. The article characterizes one-member sentences from formal grammatical and semantic standpoints, describes the main types of these sentences. In the focus of this study is the originality of syntactic structure and functioning of one-member sentences in Ulas Samchuk's prose. The in-depth analysis of the semantic-syntactic organization of the novel Maria by Ulas Samchuk has revealed that the writer often uses one-member sentences, giving them a variety of aesthetic value. The most frequently used are definite-personal, indefinite-personal, impersonal, and nominative sentences. Using these one-word sentences, the author creates landscape sketches that serve as the background on which the events unfold. Ulas Samchuk fills his story with emotions and psychology. It is revealed that one-member sentences used in monologues and reflections of characters often help to reproduce their psychological state, to convey an assessment of the depicted events. U.Samchuk most often uses this type of sentences in depicting landscapes, in dialogues and monologues. Using these constructions, the author enriches the arsenal of visual and expressive means of artistic narration.
Keywords: types of one-member sentences; definite-personal sentences; indefinite-personal sentences; generalized personal sentences; impersonal sentences